Gender Roles and Student Involvement in Malay Literature through Drama Activity (LITPAM, 2024)
Teaching drama in Brunei presents unique challenges for educators. This study explores the need for a balanced strategy that respects cultural norms and gender roles while encouraging students’ involvement. Through a qualitative analysis of researcher and educator experiences, the study highlights the impact of student participation and engagement, with boys and girls often approaching activities differently. The study suggests that tailoring activities to diverse learning styles, creating safe spaces for open conversation and encourage teamwork and respect are crucial in helping students find their voice and develop essential life skills. This paper emphasizes the importance of cultural sensitivity, an open mind and a readiness to adapt in creating transformative drama approaches. By meeting students where they are approaching the activities with an open mind, educators can empower students to discover their strength, explore new perspectives and gain a deep understanding of themselves and the world around them. The study discusses the importance of achieving this balance to maximize the impact of drama experiences in Brunei classroom.